EMPOWERING SMALL BUSINESSES IN GEORGIA: ACCESS TO FINANCE, ECONOMIC RESILIENCE, AND SUSTAINABLE GROWTH - Natia Surmanidze; Mariam Beridze; Maia Amashukeli; Keti Tskhadadze (Agora International Journal of Economical Sciences (AIJES), 2023)
The role of small businesses in the global economy is pivotal, characterized by their flexibility, rapid adaptability, and significant contribution to job creation. Small businesses worldwide often need help securing funding, particularly in regions with the most pronounced financing gap. The article discusses small business financing, emphasizing the importance of capital access and the challenges posed by limited options. The COVID-19 impact underscores the critical role of financial support for small business resilience. Georgia serves as a case study, exemplifying the concerted efforts of government agencies and international organizations in promoting small business development. The article examines initiatives like "Enterprise Georgia," the Rural Development Agency, and the Innovation and Technology Agency. The banking sector's role in facilitating small business growth and the significance of financial awareness initiatives is examined. The article highlights various measures, including the credit guarantee scheme and commercial banks' role in enhancing financial access and awareness. Green banking and capital market development for sustainable economic growth are emerging priorities. Green financing initiatives and partnerships with organizations like the Fund for Green Growth exemplify a growing commitment to sustainability.However, the article also emphasizes the need for a comprehensive approach to capital market development in Georgia to diversify financing sources and reduce reliance on the banking sector. In summary, this article underscores the indispensable role of access to finance in sustaining small businesses worldwide, focusing on the proactive efforts and collaborative endeavors in Georgia, providing a blueprint for enhancing small business development and financial sustainability.
Keywords: 330